COMFORT WOMEN : THE CAUSES OF OTHER TRADE WARS IN EAST ASIA - Mitzy, Gulia Ichikaya; Indarto, Tri Wahyuningrum (Journal of Social Political Sciences, 2020)
South Korea and Japan are the countries that have geographical proximity, with various values and cultural similarities. However, bilateral relations between the two countries are often discussed, while the main factor is the historical problem. In 2017 Japan and South Korea boycotted each other because each other, agreed to the Women's Comfort Agreement, which was agreed in 2015 and finally ended indisputably. This study uses descriptive qualitative research methods, to analyze how to implement economic collaboration that will result if an agreement is broken. Based on the results of the analysis, the issue of women's comfort made a 1965 normalization agreement for comfort women in the 2015 agreement which did not necessarily make the two countries make peace, which was questioned involving researchers not being involved in making the agreement. This has an impact on the economic relations between the two countries. Attacking each other through diplomatic representatives, asking for exports of semiconductor materials, exchanging up to stopping transportation services, advertising for boycotts of products from Japan, making developed countries even more inflamed and looking for new developments to foster mutual efforts to intervene with each other.